Alternative reproductive tactics and strategies of Glossogobius callidus (Teleostei: Gobiidae) - Okuhle Cembi; Thendo Mutshekwa; Linton F. Munyai; Phumza Ndaleni; Lubabalo Mofu (Discover Ecology, 2026)
In many animal species, males frequently have alternative reproductive tactics (ART) to maximise their reproductive success. These reproductive strategies or tactics are often characterised by differences in traits such as behaviour, physiology and morphology. However, there is very limited evidence for the occurrence of such tactics in Gobiidae. In this study, we investigated the population of Glossogobius callidus from artificial ponds located in the Lower Sundays River Valley, in the Eastern Cape, South Africa across three seasons (Winter, Spring and Summer). We found that the urogenital papilla can be used to sex G . callidus , without sacrificing the fish. Urogenital papilla of G . callidus was longer and wide in females and shorter in males. In addition, three morphologically distinct male morphs, which represented alternative reproductive tactics were identified (parental, intermediate and sneaker). There was a significant relationship between ART and the different male morphs of G . callidus . These three male morphs were distinguished by body coloration, with parental males displaying dark colouration, while sneaker males exhibited light colouration, and intermediate males showed characteristics between the two extremes. Males exhibiting dark coloured morphs were significantly heavier than those with light coloured morphs. There was a high abundance of dark morphs in Spring (355 individuals) and Summer (202 individuals), which corresponds to the reproductive season. In contrast, the high abundance of light morphs observed during winter (n = 142) suggests that alternative reproductive tactics or traits may be established prior to the breeding season. This study contributed to knowledge on the ART of G . callidus .